Moss inhabiting flea beetles (Coleoptera: Chrysomelidae: Galerucinae: Alticini) of the West Indies II: Menudos, a new genus from Puerto Rico and description of methods to collect moss inhabiting flea beetles - Linzmeier, Adelita M.; Konstantinov, Alexander S. (Zootaxa, 2020)
Menudos Linzmeier & Konstantinov, a new genus of moss inhabiting flea beetles, containing five species, three of them are new (M. illariosus, M. maricao, and M. toronegro—the type species of the genus), from Puerto Rico is described and illustrated. The new genus is compared to Aedmon Clark, Apleuraltica Bechyne, Andersonaltica Linzmeier & Konstantinov, Distigmoptera Blake and Ulrica Scherer. Aedmon barberi (Blake, 1943b) and Distigmoptera chamorrae Konstantinov & Konstantinova, 2011 are transferred to Menudos. A key to Menudos species identification is provided. Methods for collecting moss inhabiting flea beetles and other arthropods are described in detail for the first time.